2005
DOI: 10.1177/008124630503500104
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Ideation in the South African Police Service

Abstract: Little information exists regarding the suicide ideation of uniformed members of the South African Police Service (SAPS). The objectives of this study were to determine the level of suicide ideation of police members and to determine the differences between the suicide ideation of various demographic groups. Across-sectional survey design was used. Stratified random samples (W = 1781) were taken of police members of eight provinces in South Africa. The Adult Suicide Ideation Questionnaire and a biographical qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 37 publications
(38 reference statements)
1
35
0
1
Order By: Relevance
“…The rank of constable is the lowest rank in the organisation and constables might experience problems to cope with conditions in the SAPS (Pienaar & Rothmann, 2005), which might explain their higher scores on unwellness. Individuals falling in this category are still very young and have the advantage of being in a physically healthy state, not feeling stagnated in their job and still seeing the work of a police official as challenging, which contributes to a feeling of wellness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rank of constable is the lowest rank in the organisation and constables might experience problems to cope with conditions in the SAPS (Pienaar & Rothmann, 2005), which might explain their higher scores on unwellness. Individuals falling in this category are still very young and have the advantage of being in a physically healthy state, not feeling stagnated in their job and still seeing the work of a police official as challenging, which contributes to a feeling of wellness.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of suicide ideation in South Africa, Pienaar and Rothmann (2005) showed that police members who measured high on suicide ideation had the rank of constable or sergeant and had educational qualifications lower than Grade 12. Police members with the rank of constable and sergeant (and especially those with lower qualifications) might find it difficult to cope with the conditions in the SAPS, which is a conflict-prone organisation because of the transformation that is taking place.…”
Section: Perceived Wellness and Biographical Variablesmentioning
confidence: 99%
“…When experienced at clinically significant levels, suicide ideation should in itself be considered as an indication of psychological problems, even in cases where it is not viewed as a precursor to suicidal intent or self-injury (Reynolds, 1991a). In light of South Africa's exceptionally high police suicide rate, a growing emphasis is placed on the early identification of officers at risk (Pienaar & Rothmann, 2005). Hem et al (2001) recommend that in studies of suicide among police officers, suicide ideation must be investigated along with completed suicide.…”
mentioning
confidence: 99%
“…From the perspective of police members and the community, too many criminals go free because of insufficient evidence. In a study of 2 396 police members in South Africa, Pienaar (2002) found that seeing criminals go free is a severe stressor for police members. According to Louw (1997), inherent weaknesses in the South African criminal justice system contribute to a situation of crisis proportions.…”
Section: Discussionmentioning
confidence: 99%